Transcatheter Mitral Valve-in-Valve Implantations Using Inverted J-Valve - Liu, Lulu; Xiao, Bowen; Wu, Binggang; Guo, Yingqiang (Frontiers in Cardiovascular Medicine, 2022)
Background As bioprosthetic valves are being widely used, the incidence of structural valve deterioration increases, as well as the need for reoperation. Transcatheter mitral valve-in-valve implantations are being increasingly adopted as an alternative to redo-surgical mitral replacement for patients with high surgical risks. This study reports a series of transcatheter mitral valve-in-valve implantations using inverted J-valves. Methods From April 2019 to September 2021, 17 symptomatic high-risk patients with mitral bioprosthetic valve dysfunction underwent transapical transcatheter mitral valve-in-valve implantations using inverted J-valves at our institution. Results The median age was 70 years, with 76.5% being female. The median Society of Thoracic Surgeons predicted risk of mortality (STS PROM) was 17.2% (8.7–82.24%). All patients had successful transapical transcatheter mitral valve-in-valve implantations except for one intraoperative death due to left ventricle rupture. Four patients underwent simultaneous transcatheter aortic valve implantation, two of which had valve-in-valve transcatheter aortic valve implantation. There was no major complication except one case of bleeding. Thirty-day mortality was 11.8% (2/17), and 90-days mortality was 23.5% (4/17). Percentages of patients with New York Heart Association class III/IV symptoms decreased from 100 (17/17) to 20% (3/15) at 30-days. Median mitral inflow velocity was 1.95 mm/s at 30 days, compared to 2.7 mm/s at baseline. Median mitral valve effective orifice area increases from 1.5 mm at baseline to 1.85 mm at 30 days. Conclusion Transcatheter transapical valve-in-valve implantations with J-valve can be a plausible solution to failed mitral bioprosthesis with acceptable results for high-risk patients.